Immune checkpoint inhibitor-induced myocarditis and myositis in liver cancer patients: A case report and literature review - Mei, Haoran; Wen, Wu; Fang, Kang; Xiong, Yuanpeng; Liu, Weiqi; Wang, Jie; Wan, Renhua (Frontiers in Oncology, 2023)
With the development of immunotherapy, immune checkpoint inhibitors (ICIs) are widely used in clinical oncology and have achieved good results. ICIs could induce immune-related adverse events (irAEs) in cancer treatment, which warrant sufficient attention. Among them, immune myositis can manifest severe symptoms affecting the whole body, and immune myocarditis occurs with a low incidence but high fatality rate. Here we report a case of grade 3/4 adverse reactions in a patient with partial hepatectomy for malignancy after using ICIs and describe the clinical presentation, laboratory results, treatment, and prognosis. It emphasizes that clinicians should focus on being alert to irAEs in liver cancer patients who have received ICI therapy. The case we present is a 56-year-old male diagnosed with hepatocellular carcinoma. Right hepatic lobectomy was performed in April 2019. Postoperative follow-up showed that TACE combined with sorafenib (400 mg twice daily) failed to stop the recurrence of the tumor. In December 2020, the patient started to use camrelizumab injections (200mg/injection every 21 days as a cycle). 3 cycles ago, the patient had decreased muscle strength in both lower extremities with chest tightness, dyspnea, and expectoration (whitish sputum). The diagnosis was ICIs injection-induced immune myocarditis and myositis accompanied. The patient’s condition improved considerably by steroid pulse therapy timely. The case emphasizes that clinicians should focus on being alert to irAEs in liver cancer patients who have received ICI therapy.